Analysis of the situation of chicken consumption in neighborhood stores - Verjel -Carrascal, Mailin Dayana; Pacheco- Sánchez, Carlos Alberto (Universidad Francisco de Paula Santander, 2018)
In the family basket, chicken meat has become one of the main products for families in the country, therefore, the research sought to know the dynamics of the supply of chicken consumption through the descriptive methodology with a quantitative approach, for this, we worked with a population of 28 neighborhood stores located in Ocaña commune 4 according to data obtained by the Ocaña Chamber of Commerce. Among the results obtained, it is understood that the community purchases products per unit or weight, and it is also observed that more than 20% of the storekeepers manage to market 1 to 2 chickens during the day.